Systematic development of electrospun PLA/PCL fibre hybrid mats: Preparation, material characterisation and application in drug delivery - Haroosh, Hazim Jasim Mohammed; Dong, Yu (Wiley VCH, 2015)
Differing from general melt polymer blending, a sophisticated electrospinning technique to produce continuous polylactic acid (PLA) and poly(ε-caprolactone) (PCL) hybrid fibers was employed to develop favorable fibrous networks of polymer blends for the application of drug delivery. Three typical cosolvents, consisting of chloroform (CHCl3)/acetone (C3H6O), chloroform (CHCl3)/methanol (MeOH), and dichloromethane (DCM)/N,N-dimethylformamide (DMF), were employed to form high- and low-molecular-weight PCL solutions at 9  and 15 wt%/v with 8 wt%/v PLA, respectively. Such systematic development focused on investigating the effects of polymeric solution variables, such as solution viscosity, polymer molecular weight, solution concentration, polymer blend ratio, and solvent types, on fiber diameters, morphological structures, and thermal properties associated with the degree of crystallinity and rates of drug release. The results show that the formation of bead-free hybrid fibers is ascribed to the increased molecular weight and concentration of polymer solutions. The molecular weight of PCL and cosolvent type have greatly influenced the degree of crystallinity and thermal parameters such as glass transition temperature (Tg), melting temperature (Tm), crystallization temperature (Tc) of PCL components in polymer blends. Finally, the biodegradation rate is accelerated when blending PLA/PCL with a low PCL concentration of 9 wt%/v while the slower release rate of tetracycline hydrochloride drug (TCH) is revealed in the blends with a high PCL concentration of 15 wt%/v.